2018
DOI: 10.18203/2320-1770.ijrcog20180410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral contraceptives on tear film in reproductive age group women

Abstract: Background: According to WHO 2009, 60-70% women use one of the method of contraception. 8.8% to 15.4% women use oral contraceptives. Objective of present study was to investigate the effect of oral contraceptives on androgen profile and tear film parameters in females within child bearing age.Methods: Present study involve 100 healthy women between 20-45 years, who presented in family planning clinic. Two groups were made according to the use of oral contraceptive pills. Study group consist of 50 women who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…22,23 This normal androgen bioactivity is seen in normal values of tears secretion and stability in women who used combined oral contraceptives, three monthly injections, and subdermal implant hormonal contraceptives. A study by Sharma et al, 3 also found that the serum androgen level (testosterone and DHEA) was slightly decreased by 12% in the hormonal contraceptives group compared with the control, but the tear film parameters are still within normal limits. However, this study does not measure the androgen serum level of all participants, so the relationship between the type of hormonal contraceptives and androgen bioactivity on the lacrimal and meibomian gland is not yet confirmed.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…22,23 This normal androgen bioactivity is seen in normal values of tears secretion and stability in women who used combined oral contraceptives, three monthly injections, and subdermal implant hormonal contraceptives. A study by Sharma et al, 3 also found that the serum androgen level (testosterone and DHEA) was slightly decreased by 12% in the hormonal contraceptives group compared with the control, but the tear film parameters are still within normal limits. However, this study does not measure the androgen serum level of all participants, so the relationship between the type of hormonal contraceptives and androgen bioactivity on the lacrimal and meibomian gland is not yet confirmed.…”
Section: Discussionmentioning
confidence: 88%
“…A similar result was also reported by Idu et al, 10 which found no significant differences in tear secretion and tear stability between women on injectable hormonal contraceptives and women not using hormonal contraceptives. Sharma et al, 3 reported different results that they found a significant decrease in tear secretion in women using oral hormonal contraceptives (13±3 mm) than in the control group (31±7 mm/5min) with p=0.00. Nevertheless, they do not find any significant difference in TBUT value between the two groups.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our study was supported by the findings of Ihesuilor et al [15] who found that gender significantly influence tear production after the administration of bromfenac. According to Sharma, et al [16] , this could be as a result of a decrease in androgen levels in women taking oral contraceptives. It was concluded from the study that the use of oral contraceptives is an important etiological factor in pathogenesis of dry eye disease in women of reproductive age.…”
Section: Discussionmentioning
confidence: 99%